2023
DOI: 10.3389/fpsyt.2023.1153648
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like peptide-1 receptor-agonists treatment for cardio-metabolic parameters in schizophrenia patients: a systematic review and meta-analysis

Abstract: AimsWe performed this meta-analysis to evaluate the efficacy and safety of glucagon-like peptide-1 receptor-agonists (GLP-1RA) treatment on cardio-metabolic parameters among antipsychotic-treated patients with schizophrenia.MethodsWe searched the Web of Science, Cochrane Central Register of Controlled Trials, PubMed, PsycINFO, and Scopus for relevant Randomized Clinical trials (RCTs) from inception until 1 August 2022. Documents were screened for qualified articles, and all concerned outcomes were pooled as ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…A previous systematic review demonstrated that use of such agents reduced weight gain and improved key metabolism markers. 259 However, barriers exist with respect to monitoring and managing cardiometabolic risk factors in patients prescribed antipsychotic medication, and there is a need for clear guidelines and educational resources to try and address these. 260 Smoking is another major cause of ill health in people with schizophrenia.…”
Section: Treatments For Schizophrenia: Management Of Co-morbiditiesmentioning
confidence: 99%
“…A previous systematic review demonstrated that use of such agents reduced weight gain and improved key metabolism markers. 259 However, barriers exist with respect to monitoring and managing cardiometabolic risk factors in patients prescribed antipsychotic medication, and there is a need for clear guidelines and educational resources to try and address these. 260 Smoking is another major cause of ill health in people with schizophrenia.…”
Section: Treatments For Schizophrenia: Management Of Co-morbiditiesmentioning
confidence: 99%